DAMPAK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI KARAKTER SISWA SEKOLAH DASAR DI KABUPATEN LABUHANBATU - Zahroni Fatwa (CV. ADIBA AISHA AMIRA, 2024)
School is a place to socialize and learn. namely educational institutions that train students to cultivate character and facilitate students to grow and explore student potential so that they can produce a generation that is productive, creative and able to answer challenges. In our country, education is expected to be able to build the religious character of students, including Islamic education. Learning Islamic religious education is considered very urgent in the framework of building students' character values ​​who are religious humanists. The aim of this research is to answer the problem of what is the concept of Islamic education for elementary school students? How is Islamic religious education learning implemented in developing students in elementary schools? This research method uses qualitative research. Problems are discussed through literature study. Building the character of elementary school students is an effort to shape the character of students who do not separate two things that should go hand in hand, namely divine and human orientation as a form of developing human nature based on the noble values ​​of Islam. Religious character values ​​are expected to be able to lead the educational process towards a balance between the two hablun min Allah and hablun min al-nas.